Factors Associated with Suicidality Among a National Sample of Transgender Veterans. Issue 5 (15th February 2016) - Lehavot, Keren; Simpson, Tracy L.; Shipherd, Jillian C.
Abstract : Correlates of past‐year suicidal ideation and lifetime suicide risk among a national sample of transgender veterans were examined. An online, convenience sample of 212 U.S. transgender veterans participated in a cross‐sectional survey in February–May 2014. We evaluated associations between sociodemographic characteristics, stigma, mental health, and psychosocial resources with past‐year suicidal ideation and lifetime suicide plans and attempts. Participants reported high rates of past‐year suicidal ideation (57%) as well as history of suicide plan or attempt (66%). Transgender‐related felt stigma during military service and current posttraumatic stress disorder and depressive symptoms were associated with suicide outcomes as were economic and demographic factors.